Reformasi Pendidikan di Indonesia Menghadapi Tantangan Abad 21 - Venonica L. Diptoadi (Universitas Negeri Malang, 2016)
Twenty-first century which is just around the corner, will bring a lot of changes in several fields, including education. To find out what kind of changes should be done, it is necessary for us to retrace the history of education in Indonesia starting from the Dutch Colonial time to the present day. As a result we might be able to detect the problems in our educational sistem from pre-school to university level. Besides, this article is going to focus on what kind of educational system and human resources are needed in the next century. Based on that knowledge, some alternatives are given to solve the problems in our educational system to "produce" excellent human resources for the future.